Activated Carbon-Spinels Composites for Waste Water Treatment - De la Torre, Ernesto; Lozada, Ana Belén; Adatty, Maricarmen; Gámez, Sebastián (Metals (Basel ), 2018)
Nowadays, mining effluents have several contaminants that produce great damage to the environment, cyanide chief among them. Ferrites synthesized from transition metals have oxidative properties that can be used for cyanide oxidation due to their low solubility. In this study, cobalt and copper ferrites were synthesized via the precipitation method, using cobalt nitrate, copper nitrate, and iron nitrate as precursors in a molar ratio of Co or Cu:Fe = 1:2 and NaOH as the precipitating agent. The synthesized ferrites were impregnated in specific areas on active carbon. These composites were characterized using X-Ray Diffraction (XRD) and Scanning Electron Spectroscopy (SEM). The XRD results revealed a cubic spinel structure of ferrites with a single phase of cobalt ferrite and two phases (copper ferrite and copper oxides) for copper. The CoFe2O4 impregnated on active carbon reached a cyanide oxidation of 98% after 8 h of agitation; the composite could be recycled five times with an 18% decrease in the catalytic activity. In cobalt ferrites, a greater dissolution of iron than cobalt was obtained. In the case of copper ferrite, however, the copper dissolution was higher. These results confirm that ferrites and activated carbon composites are a novel alternative for cyanide treatment in mining effluents.